Model Komunikasi Pada Pendidikan Perkoperasian Bagi Anggota - Budi Styawan, Riky (Koaliansi : Cooperative Journal, 2021)
KPRI-KPKS is a cooperative that members consisting of domestic health staff profession in sumedang district such as doctor, nurse, midwife, etc. In addition, KPRI-KPKS has six business units including: Savings and Loan Units, Mini Market Units, Photocopy Units, Logistic Units, multi- purpose building rentals and canteens Units. Based on the six business units, the savings and loan unit has the largest revenue. Superior cooperatives are cooperatives that can provide welfare to members by fulfilling what their members need and want. The purpose of this research was to describe the communication model of the implementation of member education service and find out the service quality of the cooperative which would later be linked to the member participation of the KPRI-KPKS in all Units. The research method used in this study is a case study with descriptive data analysis using a qualitative approach. The results of this study Communication Services Model of KPRI-KPKS in all Unit is described in the form of TNA “Training Need Analysis” is a needs analysis specifically intended to determine what training needs are actually the priority. The concept of "Training Need Analysis" uses the concept of interactional communication model.. And the Lasswell Communication model. The efforts of KPRI-KPKS to improve the quality of KPRI-KPKS cooperative education for members in order to improve the member participation of the Cooperative. Keywords: Communication Model, Educations Service, Member Participations